Albert Sidney Johnston : Soldier of Three Republics - Roland, Charles Pierce, 1918- (Book collections on Project MUSE., 2001)
"" With a new foreword by Gary W. Gallagher Selected as one of the best one hundred books ever written on the Civil War by Civil War Times Illustrated and by Civil War: The Magazine of the Civil War Society A new, revised edition of the only full-scale biography of the Confederacy's top-ranking field general during the opening campaigns of the Civil War